Tata Kelola Keuangan Negara Di Era Post Pandemi: Kajian Hukum Atas Pengelolaan Dana Pemulihan Ekonomi Nasional - Ismarini Della purnama; Novaranty Zura Dwiputri; Walidul Halim; Irwan Triadi (Journal of Law Perspectives Review, 2025)
The COVID-19 pandemic compelled the Indonesian government to adopt extraordinary fiscal measures to maintain national economic stability. One of the key instruments was the National Economic Recovery (PEN) Program, which allocated Rp695.2 trillion in 2020 and increased in subsequent years. Although implemented under emergency conditions, the program remained subject to the principles of state financial governance mandated by national laws, particularly Law No. 1 of 2004 on State Treasury. This study examines the extent to which the principles of transparency, accountability, efficiency, and public participation were applied in the management of PEN funds during the post-pandemic period, and identifies legal and institutional challenges that hinder their implementation. Using a normative juridical approach combined with qualitative analysis of legislation, state financial reports, and audit findings from the Supreme Audit Agency (BPK), the research finds that despite adequate regulatory provisions, several gaps persist in practice. These include limited fiscal data integration, weak cross-sector oversight, inconsistent disclosure of budget realization, and insufficient mechanisms for meaningful public engagement. The study also highlights structural constraints within implementing agencies that reduce policy coherence and delay monitoring processes. Strengthening legal instruments, enhancing digital transparency systems, and improving public accountability frameworks are therefore essential to ensure effective and legitimate state financial management when responding to future crises.